Zooplankton exposure to microplastic contamination in a estuarine plume-influenced region, in Northeast Brazil. (1st April 2023) - Lima, C.D.M.; Melo Júnior, M.; Schwamborn, S.H.L.; Kessler, F.; Oliveira, L.A.; Ferreira, B.P.; Mugrabe, G.; Frias, J.; Neumann-Leitão, S.
Abstract: This work describes the spatio-temporal distribution of suspected plastic and microplastic (MP) particles in estuarine plumes and analyzes the microplastic/zooplankton ratio. Subsurface hauls with a conical-cylindrical net were deployed in the coastal area of Tamandare (Pernambuco, Brazil), covering the plume of two rivers and a bay adjacent to coral reefs. A total of 2079 suspected plastic particles were detected, mostly fibers and fragments (>60%). Organic matter digestion was made using a 30% hydrogen peroxide solution, of which approximately 50% of suspected particles were validated as MPs. The average MP abundance was significantly higher during the high rainfall season (53.8 ± 89.6 and 18.8 ± 32.3 particles/m³, respectively), with higher values registered in the plume area (108.9 ± 158.5 and 44.6 ± 55.5 particles/m³). Polymer identification using FT-IR confirmed that suspected particles were mainly polypropylene, polyamide, and polyurethane. These results confirm the hypothesis of a temporal transport variation of MPs from the river to the coastal environments, particularly since the plume influences debris input. Eleven animal phyla were identified, and the subclass Copepoda was predominant (90%), particularly the nauplius stage (70%). Over 70% of verified MPs range between 20 and 2000 μm, equivalent to the most common size of zooplanktonic organisms. Results support that coastal areas near estuarine plumes are exposed to microplastic contamination, affecting species dependent on zooplankton in marine coastal food webs. Graphical abstract: Image 1 Highlights: Microplastic input in the marine coast is strongly influenced by the river plume. More than 40% of the suspected plastic identified as 'fibers' were validated. Not all brightly colored particles can be confirmed as plastic polymers. Over 70% of the MP are in the size fraction equivalent to the zooplankton spectra. Planktivorous species are more vulnerable to exposure by MP in the high rainfall.